Family Relationships and the Three Dimensions of Subjective Wellbeing - Mega, Savinee (The Periodical of Behavioral Science, 2023)
The objective of this research is to analyze the relationship between family relationship and subjective wellbeing of Thai people, which is divided into three dimensions: life evaluation, positive affect, and negative affect. Additionally, the research aims to analyze other factors that are related with the subjective well-being. The analysis utilized data from the 2018 Social and Cultural Situation Survey conducted by the National Statistical Office, with a total sample of 10,934 individuals aged 15 years and above. The results of the ordered probit regression model indicate that a good family relationship can significantly explain subjective well-being in all three dimensions. Respondents who reported high levels of love and attachment to their families were more likely to have high levels of life satisfaction and positive affect, and less likely to have negative affect compared to those who reported low levels of family warmth. This study reflects that a warm family relationship has a significant relationship with the subjective wellbeing of Thai people in both short-term dimensions (measured by positive and negative emotions), and long-term dimensions (measured by life evaluation). Therefore, if the goal of public policy is to increase the happiness of Thai people, public or private policies that promote family cohesion or relationship, should be considered an important priority for Thailand.